Insertable cardiac monitor with a long sensing vector: Impact of obesity on sensing quality and safety - Bisignani, Giovanni; De Bonis, Silvana; Pierre, Bertrand; Lau, Dennis H.; Hofer, Daniel; Sanfins, Victor Manuel; Hain, Andreas; Cabanas, Pilar; Martens, Eimo; Berruezo, Antonio; Eschalier, Romain; Milliez, Paul; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Fat layers in obese patients can impair R-wave detection and diagnostic performance of a subcutaneous insertable cardiac monitor (ICM). We compared safety and ICM sensing quality between obese patients [body mass index (BMI) ≥ 30 kg/m2] and normal-weight controls (BMI <30 kg/m2) in terms of R-wave amplitude and time in noise mode (noise burden) detected by a long-sensing-vector ICM. Materials and methods Patients from two multicentre, non-randomized clinical registries are included in the present analysis on January 31, 2022 (data freeze), if the follow-up period was at least 90 days after ICM insertion, including daily remote monitoring. The R-wave amplitudes and daily noise burden averaged intraindividually for days 61–90 and days 1–90, respectively, were compared between obese patients (n = 104) and unmatched (n = 268) and a nearest-neighbour propensity score (PS) matched (n = 69) normal-weight controls. Results The average R-wave amplitude was significantly lower in obese (median 0.46 mV) than in normal-weight unmatched (0.70 mV, P < 0.0001) or PS-matched (0.60 mV, P = 0.003) patients. The median noise burden was 1.0% in obese patients, which was not significantly higher than in unmatched (0.7%; P = 0.056) or PS-matched (0.8%; P = 0.133) controls. The rate of adverse device effects during the first 90 days did not differ significantly between groups. Conclusion Although increased BMI was associated with reduced signal amplitude, also in obese patients the median R-wave amplitude was >0.3 mV, a value which is generally accepted as the minimum level for adequate R-wave detection. The noise burden and adverse event rates did not differ significantly between obese and normal-weight patients. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT04075084 and NCT04198220.